Estimating Global Burden of Disease due to congenital anomaly: an analysis of European data. Issue 1 (30th June 2017) - Boyle, Breidge; Addor, Marie-Claude; Arriola, Larraitz; Barisic, Ingeborg; Bianchi, Fabrizio; Csáky-Szunyogh, Melinda; de Walle, Hermien E K; Dias, Carlos Matias; Draper, Elizabeth; Gatt, Miriam; Garne, Ester; Haeusler, Martin; et al.
Abstract : Objective: To validate the estimates of Global Burden of Disease (GBD) due to congenital anomaly for Europe by comparing infant mortality data collected by EUROCAT registries with the WHO Mortality Database, and by assessing the significance of stillbirths and terminations of pregnancy for fetal anomaly (TOPFA) in the interpretation of infant mortality statistics. Design, setting and outcome measures: EUROCAT is a network of congenital anomaly registries collecting data on live births, fetal deaths from 20 weeks' gestation and TOPFA. Data from 29 registries in 19 countries were analysed for 2005–2009, and infant mortality (deaths of live births at age <1 year) compared with the WHO Mortality Database. Eight EUROCAT countries were excluded from further analysis on the basis that this comparison showed poor ascertainment of survival status. Results: According to WHO, 17%–42% of infant mortality was attributed to congenital anomaly. In 11 EUROCAT countries, average infant mortality with congenital anomaly was 1.1 per 1000 births, with higher rates where TOPFA is illegal (Malta 3.0, Ireland 2.1). The rate of stillbirths with congenital anomaly was 0.6 per 1000. The average TOPFA prevalence was 4.6 per 1000, nearly three times more prevalent than stillbirths and infant deaths combined. TOPFA also impacted on the prevalence of postneonatal survivors with non-lethal congenital anomaly. Conclusions: By excluding TOPFA and stillbirths from GBD years of life lost (YLL) estimates, GBD underestimates the burden of disease due to congenital anomaly, and thus declining YLL over time may obscure lack of progress in primary, secondary and tertiary prevention.